Pengaruh Corporate Governance terhadap Environmental Disclosure dengan Environmental Performance sebagai Variabel Moderating - Nana Nofianti; Lia Uzliawati; Sarka S (TRIKONOMIKA, 2015)
The purpose of this study is to examine the effect that caused the application corporate governance (Measured by the corporate governance index of the IICG) in the exercises oversight of the conduct of the environmental disclosure (Measured by IER Index of Suhardjanto), and to determine whether environmental performance the company (Measured with PROPER) as a moderating variable can be moderate influence of application corporate governance to environmental disclosure of company PROPER participants and listed in Indonesia Stock Exchange during 2010-2013 period. The method used to collect data is the purposive sampling method. Sampling criteria in this study is the Company that participate in Program Performance Rating (PROPER) 2010-2013, which listing in Indonesia Stock Exchange (IDX). The sample consists of 27 Companies selected from the population as much data as 28 the company. The results showed that: 1) corporate governance significant positive effect on environmental disclosure, and 2) environmental performance may moderate the influence of corporate governance to environmental disclosure.